Sports Participation For Hong Kong Women And Hong Kong Initiatives: 對香港女性參與運動之探討 - LEUNG, Mee Lee (Asian Journal of Physical Education & Recreation, 1995)
LANGUAGE NOTE | Document text in English; abstract also in Chinese. Historically, sports was globally understood within the context of a masculine value system both in the Eastern and Western Societies. The ’Ying’ and the ’Yang’ stand for female and male in the Chinese culture implied that the female are more fragile and submissive where as the male being more aggressive and stronger. With 90% of the population in Hong Kong being Chinese, the cultural belief in a Chinese society that "Women’s place should be in the home" has confined women to attend household chores and child bearing activities. In early 20th century, with the changing role of women in China and especially in Hong Kong, women are more active that they were a decade ago. Women are equal nowadays in a wide range of activities because they are better educated, play a more committed role and live a more active life. Thus, their participation in sports has increased in the past decade both in recreation and in competition. This paper attempts to report on Hong Kong women’s participation in major games and also to recommend strategies which can further enhance women’s place in sports. 歷史上，無論東西方社會，運動廣泛地被視為屬於雄性的項目。正如中國以陰陽來代表女男一樣，女性被認為較順從和脆弱的，而男性則較強壯和具攻擊性。在九成人口都是中國人的香港社會中，「女性應該留在家裡」的觀念曾規限著女性須要處理家務和照顧孩子的責任。踏入20世紀，女性對社會事務的參與也開始積極起來。時至今日，香港的女性在多方面都能跟男性般獲得平等對待。她們不單止得到較佳的敎育機會， 在社會的角色也越來越重要。因此，無論在運動比賽及健體活動上，女性的參與比十年前的大為提高。究竟香港女性過去在主要運動競賽上的參與情況和未來女性在運動發展上方針應該如何?這都是本文探討的綱領。